Análise do potencial bioativo de vidros à base de borofosfato - Silva, Maurício Dalla Costa Rodrigues da (2019)
The use of phosphate and borate glasses on regeneration of bone tissue has been researched for the past years due to its potential of being reabsorbed by the organism during the recovery process of affected tissues. This study aims to evaluate the in vitro bioactive potential of borophosphate glasses with Ca/P ratios of 0,6 (BV1), 1,0 (BV2) and 1,4 (BV3), as well as its structure, processing, physical, thermal and surface properties. The materials were melted at 1200°C on porcelain crucible followed by quenching in two different routes: air (piece) and water (frite). The glasses quenched on air were annealed at 600°C during 1 hour. The frites were grinding in ball mill for 1 hour at 60 rpm, sieving at 25 m and the process yield was calculated. The DSC was performed in order to determinate the glass transition temperature of the materials and its structure were analyzed by XRD and FTIR. The materials densities were determined by gas pycnometry, and the specific surface area and the pores features by BET. The in vitro essays were performed by soaking the glass pieces on SBF during 7, 14, 21 and 28 days, follow by media pH measurement. determination of Ca and P by ICP-OES, solubility profiles of the materials and the analysis of surface changes by MEV/EDS. The developed materials presented amorphous structures and boron-phosphate characteristic absorption bands, with glass transition temperature between 500-600°C. The materials grinding exhibited yields of 48,5, 65,7 and 73,7% for the glasses BV1, BV2 and BV3 respectively. The glasses densities revealed significant differences (p≤0,05) in terms of Ca/P ratio variability, the specific surface area and pore features were lesser than the results obtained for sol-gel glasses. The solubility of the materials presented linear relationship with soaking time, being glass BV1 the most soluble. The Ca and P concentrations along the in vitro essays indicated that calcium phosphates deposits occurred on the surface and also the glass network dissolution. Surface analysis by MEV/EDS evidenced hydroxyapatite formation on glass BV1 between 21-28 days of soaking. This study concluded that the reduction of Ca/P ratio on boron-phosphate glasses compositions had as effect the increase of solubility of the material and improvements on hydroxyapatite formation on acellular in vitro media.